An exploratory study into the efficacy and implementation feasibility of vehicle financing using the concept of musharakah mutanaqisah - Thalia Rohaina Abdul Latiff (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2013)
There is a growing interest among the researchers in Islamic finance and banking, specifically, after the world economy downturn. One of those areas which have not yet been covered by them is the application of vehicle financing under the pretext of musharakah mutanaqisah particularly in Malaysia in which this study attempts to explore. The study uses the qualitative method by which the researcher interviewed eight informants who are bankers and experts in the field of Islamic banking and finance on legal constraints, Shariah argumentation, and product accessibility and feasibility. The findings of the study reveal base on the informants' responses that, vehicle financing can be workable using the concept proposed by the study on long run as people getting acquainted with it in Malaysia or in other Muslim countries. Only two informants were of the opinion that, the concept cannot take a root in Malaysian soil or in any other places, supporting their argument that people would not accept or understand it even if introduced. One of informants said, the problem with the concept in Malaysia is because it is at its infant stage. In conclusion, the researcher suggests a plethora of studies to be conducted in this area for her knowledge that there is not enough research works in vehicle financing with musharakah mutanaqisah so as to open people's horizon in understanding the issue more and more.